Dynamic changes of the gut microbial colonization in preterm infants with different time points after birth - Khan, Adnan; Mi, Hongying; Gao, Fei; Hu, Qi; Gu, Xia; Ma, Fei; Qu, LiuHong; Li, Sitao; Dai, Yiheng; Hao, Hu (Frontiers in Microbiology, 2023)
Risks associated with preterm birth are unevenly distributed across all gestations. At earlier gestational ages, complications such as necrotizing enterocolitis (NEC) and late-onset sepsis (LOS) conditions are significantly more common and are associated with a shift in the composition of the gut microbiome. Conventional bacterial culture techniques demonstrate that the colonization of the gut microbiota of preterm infants differs significantly from that of healthy-term infants. The current study aimed to investigate the impact of preterm infancy on the dynamic changes of fecal microbiota in preterm infants at different time points (1, 7, 14, 21, 28, and 42 days) after birth. We selected 12 preterm infants hospitalized in the Sixth Affiliated Hospital of Sun Yat-sen University from January 2017 to December 2017. A total of 130 fecal specimens from preterm infants were analyzed using 16S rRNA gene sequencing. We found that the colonization process of fecal microbiota in preterm infants is highly dynamic at different time points after birth, i.e., Exiguobacterium, Acinetobacter, and Citrobacter showed a declining abundance pattern with the advancement of age, while the bacterial groups of Enterococcus (Klebsiella and Escherichia coli) gradually grew and became the main microbiota during the development of fecal microbiota in preterm infants at the age of 42 days. Furthermore, the colonization of intestinal Bifidobacteria in preterm infants was relatively late and did not rapidly become the predominant microbiota. Moreover, the results also showed the presence of Chryseobacterium bacterial group, whose colonization was different in different time point groups. Conclusively, our findings deepen our comprehension and offer new perspectives on targeting particular bacteria in the treatment of preterm infants at different time points after birth.